Corrigendum to “The influence of crustal recycling on the molybdenum isotope composition of the Earth's mantle” [Earth Planet. Sci. Lett. 595 (2022) 117760] - Remco C. Hin; Kate E.J. Hibbert; Shuo Chen; Matthias Willbold; Morten B. Andersen; Ekaterina S. Kiseeva; Bernard J. Wood; Yaoling Niu; Kenneth W.W. Sims; Tim Elliott (Earth and Planetary Science Letters, 2023)

Deficiency of T-type voltage-gated calcium channels results in attenuated weight gain and improved endothelium-dependent dilatation of resistance vessels induced by a high-fat diet in mice - Kristoffer Rosenstand; Kenneth Andersen; Rasmus Terp; Peter Gennemark; Ditte Gry Ellman; Anna Reznichenko; Kate Lykke Lambertsen; Paul M. Vanhoutte; Pernille B. L. Hansen; Per Svenningsen (Journal of Physiology and Biochemistry, 2020)

Correction to: The carbon pump supports high primary production in a shallow lake - Mikkel René Andersen; Theis Kragh; Kenneth Thorø Martinsen; Emil Kristensen; Kaj Sand-Jensen (Aquatic Sciences, 2019)

The carbon pump supports high primary production in a shallow lake - Mikkel René Andersen; Theis Kragh; Kenneth Thorø Martinsen; Emil Kristensen; Kaj Sand-Jensen (Aquatic Sciences, 2019)

Water temperature dynamics and the prevalence of daytime stratification in small temperate shallow lakes - Kenneth Thorø Martinsen; Mikkel René Andersen; Kaj Sand-Jensen (Hydrobiologia, 2019)

Deletion of T-type calcium channels Cav3.1 or Cav3.2 attenuates endothelial dysfunction in aging mice - Anne D. Thuesen; Kenneth Andersen; Kristina S. Lyngsø; Mark Burton; Charlotte Brasch-Andersen; Paul M. Vanhoutte; Pernille B. L. Hansen (Pflügers Archiv - European Journal of Physiology, 2018)

High rates and close diel coupling of primary production and ecosystem respiration in small, oligotrophic lakes - Kenneth Thorø Martinsen; Mikkel René Andersen; Theis Kragh; Kaj Sand-Jensen (Aquatic Sciences, 2017)

Importance of mind-muscle connection during progressive resistance training - Joaquin Calatayud; Jonas Vinstrup; Markus Due Jakobsen; Emil Sundstrup; Mikkel Brandt; Kenneth Jay; Juan Carlos Colado; Lars Louis Andersen (European Journal of Applied Physiology, 2016)

T-type Ca2+ channels facilitate NO-formation, vasodilatation and NO-mediated modulation of blood pressure - Per Svenningsen; Kenneth Andersen; Anne D. Thuesen; Hee-Sup Shin; Paul M. Vanhoutte; Ole Skøtt; Boye L. Jensen; Caryl Hill; Pernille B. L. Hansen (Pflügers Archiv - European Journal of Physiology, 2014)

Meta‐barcoding of ‘dirt’ DNA from soil reflects vertebrate biodiversity - KENNETH ANDERSEN; KAREN LISE BIRD; MORTEN RASMUSSEN; JAMES HAILE; HENRIK BREUNING‐MADSEN; KURT H. KJÆR; LUDOVIC ORLANDO; M. THOMAS P. GILBERT; ESKE WILLERSLEV (Molecular Ecology, 2012)
DNA molecules originating from animals and plants can be retrieved directly from sediments and have been used for reconstructing both contemporary and past ecosystems. However, the extent to which such ‘dirt’ DNA reflects taxonomic richness and structural diversity remains contentious. Here, we couple second generation high‐throughput sequencing with 16S mitochondrial DNA (mtDNA) meta‐barcoding, to explore the accuracy and sensitivity of ‘dirt’ DNA as an indicator of vertebrate diversity, from soil sampled at safari parks, zoological gardens and farms with known species compositions. PCR amplification was successful in the full pH range of the investigated soils (6.2 ± 0.2 to 8.3 ± 0.2), but inhibition was detected in extracts from soil of high organic content. DNA movement (leaching) through strata was evident in some sporadic cases and is influenced by soil texture and structure. We find that DNA from the soil surface reflects overall taxonomic richness and relative biomass of individual species. However, one species that was recently introduced was not detected. Furthermore, animal behaviour was shown to influence DNA deposition rates. The approach potentially provides a quick methodological alternative to classical ecological surveys of biodiversity, and most reliable results are obtained with spatial sample replicates, while relative amounts of soil processed per site is of less importance.

Islands in the ice: detecting past vegetation on Greenlandic nunataks using historical records and sedimentary ancient DNA Meta‐barcoding - TINA JØRGENSEN; KURT H. KJÆR; JAMES HAILE; MORTEN RASMUSSEN; SANNE BOESSENKOOL; KENNETH ANDERSEN; ERIC COISSAC; PIERRE TABERLET; CHRISTIAN BROCHMANN; LUDOVIC ORLANDO; M. THOMAS P. GILBERT; ESKE WILLERSLEV (Molecular Ecology, 2012)
Nunataks are isolated bedrocks protruding through ice sheets. They vary in age, but represent island environments in ‘oceans’ of ice through which organism dispersals and replacements can be studied over time. The J.A.D. Jensen’s Nunataks at the southern Greenland ice sheet are the most isolated nunataks on the northern hemisphere – some 30 km from the nearest biological source. They constitute around 2 km 2 of ice‐free land that was established in the early Holocene. We have investigated the changes in plant composition at these nunataks using both the results of surveys of the flora over the last 130 years and through reconstruction of the vegetation from the end of the Holocene Thermal Maximum (5528 ± 75 cal year BP) using meta‐barcoding of plant DNA recovered from the nunatak sediments ( sed aDNA). Our results show that several of the plant species detected with sed aDNA are described from earlier vegetation surveys on the nunataks (in 1878, 1967 and 2009). In 1967, a much higher biodiversity was detected than from any other of the studied periods. While this may be related to differences in sampling efforts for the oldest period, it is not the case when comparing the 1967 and 2009 levels where the botanical survey was exhaustive. As no animals and humans are found on the nunataks, this change in diversity over a period of just 42 years must relate to environmental changes probably being climate‐driven. This suggests that even the flora of fairly small and isolated ice‐free areas reacts quickly to a changing climate.

A comparative study of ancient sedimentary DNA, pollen and macrofossils from permafrost sediments of northern Siberia reveals long‐term vegetational stability - TINA JØRGENSEN; JAMES HAILE; PER MÖLLER; ANDREI ANDREEV; SANNE BOESSENKOOL; MORTEN RASMUSSEN; FRANK KIENAST; ERIC COISSAC; PIERRE TABERLET; CHRISTIAN BROCHMANN; NANCY H. BIGELOW; KENNETH ANDERSEN; et al. (Molecular Ecology, 2012)
Although ancient DNA from sediments ( sed aDNA) has been used to investigate past ecosystems, the approach has never been directly compared with the traditional methods of pollen and macrofossil analysis. We conducted a comparative survey of 18 ancient permafrost samples spanning the Late Pleistocene (46–12.5 thousand years ago), from the Taymyr Peninsula in northern Siberia. The results show that pollen, macrofossils and sed aDNA are complementary rather than overlapping and, in combination, reveal more detailed information on plant palaeocommunities than can be achieved by each individual approach. Sed aDNA and macrofossils share greater overlap in plant identifications than with pollen, suggesting that sed aDNA is local in origin. These two proxies also permit identification to lower taxonomic levels than pollen, enabling investigation into temporal changes in species composition and the determination of indicator species to describe environmental changes. Combining data from all three proxies reveals an area continually dominated by a mosaic vegetation of tundra‐steppe, pioneer and wet‐indicator plants. Such vegetational stability is unexpected, given the severe climate changes taking place in the Northern Hemisphere during this time, with changes in average annual temperatures of >22 °C. This may explain the abundance of ice‐age mammals such as horse and bison in Taymyr Peninsula during the Pleistocene and why it acted as a refugium for the last mainland woolly mammoth. Our finding reveals the benefits of combining sed aDNA, pollen and macrofossil for palaeovegetational reconstruction and adds to the increasing evidence suggesting large areas of the Northern Hemisphere remained ecologically stable during the Late Pleistocene.

Urban Influences on Stream Chemistry and Biology in the Big Brushy Creek Watershed, South Carolina - Gregory P. Lewis; Jennifer D. Mitchell; C. Brannon Andersen; Dennis C. Haney; Min-Ken Liao; Kenneth A. Sargent (Water, Air, & Soil Pollution, 2007)